The Talisman of Troy : Heroes to the Death - Manfredi, Valerio Massimo; Translated from the Italian by Christine Feddersen-Manfredi (London Pan Books, 2004)
Another grandiose and brutal epic of the ancient world from the bestselling author of the 'Alexander' trilogy, Spartan and The Last Legion
Include Maps and Glossary
Keywords: Italy